FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN:SERIKAT PEKERJA, HUBUNGAN INDUSTRIAL DAN KOMUNIKASI (LITERATURE REVIEW MSDM) - Jumawan Jumawan; Hadita, Berliana Febrianti, Diana Noviyanti, Evi Permatasari, Dyah Pratiwi (Adisam Publisher, 2024)
Previous research or relevant research is very important in research or scientific articles. Previous research or relevant research functions to strengthen theories and phenomena of relationships or influences between variables. This article reviews the factors that influence Employee Job Satisfaction, namely: Labor Unions, Industrial Relations and Communication, a study of the Human Resources Management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Labor Unions influence Employee Job Satisfaction; 2) Industrial Relations influences Employee Job Satisfaction; and 3) Communication influences employee job satisfaction